Analysis of Behavioural Profile of Hens with the Use of Computer Software - I Rozempolska-Rucinska; A Bownik; T Prochniak; G Zieba; B Slaska; K Kasperek; A Kozak (Brazilian Journal of Poultry Science)
ABSTRACT The aim of the study was to evaluate the emotional reactivity of hens with the use of physical parameters such as movement velocity and position of the selected parts of the body analysed by computer software - Tracker®. 200 Rhode Island White hens kept individually in a laying hen breeding farm were used in the study. The analysis of hens behaviour was performed with the use of Novel Object Test. Afterwards the video clips were analysed to determine behavioural reactivity with the use of Tracker® software by analysis of two control points: the upper part of the head and the peak of the tail. The results suggest that it is possible to use Tracker® software for evaluation of hens behavioural profile and this sort of analysis enables to classify hens to the groups of timid or curious/courageous birds based on the parameters of movement velocity of the upper part of the head and the peak of the tail and on the basis of the ratio between the position of the head and the tail.